MicroRNA-510 mediated negative regulation of Caveolin-1 in fibroblasts promotes aggressive tumor growth - King, Brooke; Krisanits, Bradley A.; Guo, Qi J.; Blake, Bobbie; Nogueira, Lourdes M.; Jolly, Gurbani; Satterwhite, Arabia; Turner, David P.; Hoffman, Stanley; Evans-Knowell, Ashley; Findlay, Victoria J. (Frontiers in Immunology, 2023)
In the US, despite the recent decline in breast cancer deaths, a persistent mortality disparity exists between black and white women with breast cancer, with black women having a 41% higher death rate. Several studies are now reporting that racial disparities can exist independent of socioeconomic and standard of care issues, suggesting that biological factors may be involved. Caveolin-1 (Cav1) loss in the tumor stromal compartment is a novel clinical biomarker for predicting poor outcome in breast cancer including triple negative subtype, however the mechanism of Cav1 loss is unknown. We previously identified miR-510-5p as a novel oncomir and propose here that the high levels observed in patients is a novel mechanism leading to stromal Cav1 loss and worse outcomes. Cav1 was identified as a direct target of miR-510-5p through luciferase, western blot and qPCR assays. Stromal cross talk between epithelial cells and fibroblasts was assessed in vitro using transwell coculture assays and in vivo using xenograft assays. We found that Cav1 is a direct target of miR-510-5p and that expression in fibroblasts results in an 'activated' phenotype. We propose that this could be important in the context of cancer disparities as we also observed increased levels of circulating miR-510-5p and reduced levels of stromal Cav1 in black women compared to white women with breast cancer. Finally, we observed a significant increase in tumor growth when tumor cells were coinjected with miR-510-5p expressing cancer associated fibroblasts in vivo. In conclusion, we propose that miR-510-5p mediated negative regulation of Cav1 in fibroblasts is a novel mechanism of aggressive tumor growth and may be a driver of breast cancer disparity.